Manajemen Kurikulum Dalam Peningkatan Mutu Pendidikan Kesetaraan Tingkat Wustho Pada Pondok Pesantren At-Thohariyah Sodong Pandeglang - Syafe'i; H.B. Syafuri; Yus'aini (Formosa Journal of Social Sciences (FJSS), 2022)
The aims of this research are: 1) To find out the curriculum management of Pondok Pesantren At-Thohariyah Sodong Pandeglang. 2) To find out the Implementation of Islamic Boarding School Curriculum Management Implementation in order to improve the quality of wustho level equality education carried out by the At-Thohariyah Islamic Boarding School Sodong Pandeglang. 3) To find out the Supporting and Inhibiting Factors of Curriculum Management in Pondok Pesantren At-Thohariyah Sodong Pandeglang. This study uses a qualitative approach with natural characteristics (Natural Setting) as a direct, descriptive data source, in this study, the type of research used is a case study, namely an intensive description and analysis of certain phenomena or social units such as individuals, groups, institutions or communities. The results of the study can be concluded that. 1) The curriculum of the At-Thohariyah Islamic Boarding School is based on the applicable laws and regulations. Among the rules and regulations that form the basis for the preparation and development of the curriculum are Law number 20 of 2003 concerning the National Education System, Government Regulation of the Republic of Indonesia Number 55 of 2007 concerning Religious Education and Religious Education, Regulation of the Minister of Religion of the Republic of Indonesia Number 13 of 2014 concerning Religious Education Islam. 2) Darul Muttaqin Islamic boarding school still maintains its traditions and implements a modern management system. It can be stated that various activity programs in Islamic boarding schools have been formed with planning, organizing, implementing and controlling. ; 3) In the implementation of Islamic boarding school curriculum management at Pondok Pesantren At-Thohariyah Sodong Pandeglang there are supporting factors and also inhibiting factors